Immune correlates analysis of mRNA-1345 RSV vaccine efficacy clinical trial - Ma, Chong; Du, Jiejun; Lan, Lan; Kapoor, Archana; Marc, Gonzalo Perez; Jimenez, Gilberto; Duncan, Christopher J. A.; Le Cam, Nancy; Lin, Nina; Priddy, Frances; Garg, Sanjay; Stoszek, Sonia K.; et al. (Nature communications, 2025)
Identifying an immunologic marker as a correlate of protection (CoP) for RSV vaccination is important. In the pivotal phase 3 trial, the mRNA-1345 vaccine demonstrated efficacy against RSV in older adults (NCT05127434). Here, we evaluate neutralizing antibodies (nAb) against RSV-A and -B, and IgG binding antibodies (bAb) to RSV fusion antigens as correlates of risk (CoR) and CoP against the pivotal trial’s efficacy endpoints of RSV lower respiratory tract disease with ≥2 or ≥3 signs/symptoms (RSV-LRTD-2+ and −3 + ) and acute respiratory disease (RSV-ARD). Day 29 RSV nAb and prefusion (preF) IgG demonstrate consistent inverse correlates with RSV endpoint occurrence. Day 29 point estimates (95% CIs) of the hazard ratio of each endpoint (RSV-LRTD-2 + , RSV-LRTD-3 + , RSV-ARD) per 10-fold increase in RSV-A nAb are 0.44 (0.30-0.65), 0.41 (0.20-0.84), and 0.45 (0.28-0.71), respectively, similar to RSV-B nAb and preF IgG. These results demonstrate Day 29 RSV nAb and preF IgG are CoRs and support their role as CoPs against RSV endpoints. Identifying an immunologic marker as a correlate of protection (CoP) for RSV vaccination is important. Here, the authors demonstrate RSV neutralizing antibodies and RSV prefusion IgG binding antibodies as CoP for mRNA vaccination against RSV disease.